Ultrasound-guided cryoablation of early breast cancer: safety, technical efficacy, patients’ satisfaction, and outcome prediction with MRI/CEM: a pilot case-control study - Francesca Galati; Marcella Pasculli; Roberto Maroncelli; Veronica Rizzo; Giuliana Moffa; Bruna Cerbelli; Giulia d’Amati; Carlo Catalano; Federica Pediconi (European Radiology Experimental)
Abstract Background This pilot prospective study aimed to evaluate ultrasound-guided cryoablation of breast cancer (BC) by assessing: (i) technical efficacy as the presence of necrosis in surgical specimens and rate of complete tumor ablation; (ii) safety as incidence and severity of complications; and (iii) patients’ satisfaction using a dedicated questionnaire. In addition, (iv) we tested the capability of magnetic resonance imaging (MRI) or contrast-enhanced mammography (CEM) to predict cryoablation efficacy. Methods From 07/2022 to 01/2023, we enrolled 20 patients with early-stage BC scheduled for breast surgery. Ten of them, with a cryo-feasible cancer location, were sent to cryoablation (cryo-group) and ten to routine surgical practice (control group). Both groups underwent surgery and were asked to answer a satisfaction questionnaire. Results Of eleven patients screened for cryoablation, only one refused to be treated at another hospital (acceptance rate 10/11, 91%). Surgery was quadrantectomy in 19 cases and mastectomy in 1. In the cryo-group, the procedure was completed and steatonecrosis was observed in 10/10 cases, with complete tumor ablation in nine of them. The post-procedural status was evaluated with MRI in five patients, with CEM in four patients, and with ultrasound in one patient who refused MRI and CEM. MRI or CEM correctly predicted complete cryoablation in eight patients and incomplete cryoablation in one patient. Patients in both groups did not have serious complications and responded positively to satisfaction questionnaires. Conclusion Ultrasound-guided cryoablation of early-stage BC is well accepted by patients, effective, and safe. MRI and CEM were able to predict the procedure's technical efficacy. Trial registration https://clinicaltrials.gov/study/NCT05727813 updated February 14, 2023. Relevance statement Our pilot study showed that ultrasound-guided cryoablation is a promising nonsurgical alternative for treating early-stage BC. Key Points Ultrasound-guided cryoablation was effective and safe in early BC patients. The procedure was well-tolerated, with low morbidity and high patient satisfaction. MRI and CEM predicted cryoablation efficacy, in accordance with histopathologic findings. Cryoablation can be considered a potential alternative to surgery in selected patients. Graphical Abstract